2012
DOI: 10.1002/jts.21680
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for PTSD, anxiety, and depression among adolescents in gaza

Abstract: The present study examined among adolescents in Gaza the relationship between exposure to war stressors and psychological distress as well as the effects of age, gender, and socioeconomic status. Data were collected from a sample of 139 adolescents 12 to 17 years old. Results showed that adolescents reported elevated levels of intrusion, avoidance, and depression compared to levels in communities not affected by war in the recent past. The proportion scoring within the clinical range of posttraumatic stress di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 39 publications
12
56
2
3
Order By: Relevance
“…Further, the fact that trauma-related memory quality and PTSD symptoms were assessed at the same time is an important limitation for this mediation analysis. Although a measure of PTSD symptoms used in this study (CRIES) has shown adequate reliability and validity in Palestinian samples (Kolltveit et al, 2012), it showed relatively modest reliability in this trial.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Further, the fact that trauma-related memory quality and PTSD symptoms were assessed at the same time is an important limitation for this mediation analysis. Although a measure of PTSD symptoms used in this study (CRIES) has shown adequate reliability and validity in Palestinian samples (Kolltveit et al, 2012), it showed relatively modest reliability in this trial.…”
Section: Discussionmentioning
confidence: 86%
“…On this self-report questionnaire, based on DSM-IV criteria, children evaluated on a 4-point scale how often they had experienced a particular symptom over the last two weeks (0 =  not at all , 1 =  rarely , 3 =  sometimes , 5 =  often ). CRIES has shown adequate reliability and validity in Palestinian samples (Kolltveit et al, 2012). Cronbach’s α was .63…”
Section: Methodsmentioning
confidence: 99%
“…In studies with participants from the Middle East, an association is seen between mental disorders and various socioeconomic variables (10, 4148) and also traumatic events (10, 41, 42, 44, 47). In the present study women had a significantly higher severity of depression and generalized anxiety than men and female gender was a significant predictor for GAD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Contributory factors to the higher prevalence during adolescence of depressive symptoms and mood disorders among girls compared to boys are age-at-onset and onset of puberty [61-63]. Edwards et al [18] have showed that that pubertal development moderates environmental influences on depressive symptoms.…”
Section: Serotonergic Regulationmentioning
confidence: 99%